MENUMBUHKAN JIWA FINANCIAL MANAGEMENT MELALUI GAME EDUKASI DI PANTI ASUHAN DOMPET YATIM DAN DHUAFA PAMULANG - Aprilia, Dea; Saputra, Elman; Andania, Nadia; Rizki Ramadan, Syahdan; Septanta, Rananda (Tensile : Jurnal Pengabdian Kepada Masyarakat, 2024)
The Community Service Student Research aims to evaluate the use of educational games in enhancing children's understanding of financial management at the Dompet Yatim and Dhuafa Orphanage in Pamulang. Conducted by a team of accounting students from Pamulang University, this activity focuses on fostering awareness of and skills in financial management from an early age. Through socialization, material presentations, and the application of educational games, the evaluation indicates a significant improvement in the children's understanding and participation. In conclusion, educational games prove to be effective tools for enjoyable and beneficial learning, while future development suggestions involve engaging more stakeholders for broader social impact.